Analyzing the Authority Relationship Between the Center and Regions in the Reconstruction of the Execution of Decisions in Industrial Relations Dispute Resolution Cases Based on Progressive Law - Ibnu Affan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
The enforcement of general civil procedural law in the execution process of Industrial Relations Dispute Resolution (PPHI) cases, as mandated by Article 57 of the PPHI Law, has resulted in a slow execution process. Based on this, there is a need for adequate political awareness among stakeholders to carry out the reconstruction of the legal execution of PPHI case decisions. In order for this legal reconstruction movement to arise from the nation's political will, it is necessary to implement political policies. Based on the above explanation, the issues in this research can be formulated as follows: 1) How is the current implementation of the execution of decisions in industrial relations dispute resolution cases?; 2) What are the weaknesses in its implementation?; 3) What is the ideal reconstruction of the execution of decisions in industrial relations dispute resolution cases based on progressive legal justice? This research is descriptive, using empirical legal research and a socio-legal juridical approach. The research data sources are obtained from primary and secondary data. To collect primary data, observations and interviews are conducted, while obtaining secondary data involves studying legislation, jurisprudence, research results, academic works, dictionaries, and other relevant materials. This research will ultimately result in an ideal reconstruction of the execution of PPHI case decisions based on progressive legal justice, which will be incorporated into articles in the amendment of the PPHI Law, including: regulating the direct seizure of immovable property without specifying a limit on the amount of seizure by reconstructing Article 197 paragraph (1) HIR/Article 208 paragraph (1) RBg, exempting execution fees for claims worth IDR 150,000,000 (one hundred and fifty million Indonesian rupiahs) or more by reconstructing Article 58 of the PPHI Law, and prohibiting legal remedies such as Judicial Review by reconstructing Article 66 of the Supreme Court Law.